Two Patients With History of STEC‐HUS, Posttransplant Recurrence and Complement Gene Mutations. Issue 8 (3rd June 2013) - Alberti, M.; Valoti, E.; Piras, R.; Bresin, E.; Galbusera, M.; Tripodo, C.; Thaiss, F.; Remuzzi, G.; Noris, M.
Abstract: Hemolytic uremic syndrome (HUS) is a disease of microangiopathic hemolytic anemia, thrombocytopenia and acute renal failure. About 90% of cases are secondary to infections by Escherichia coli strains producing Shiga‐like toxins (STEC‐HUS), while 10% are associated with mutations in genes encoding proteins of complement system (aHUS). We describe two patients with a clinical history of STEC‐HUS, who developed end‐stage renal disease (ESRD) soon after disease onset. They received a kidney transplant but lost the graft for HUS recurrence, a complication more commonly observed in aHUS. Before planning a second renal transplantation, the two patients underwent genetic screening for aHUS‐associated mutations that revealed the presence of a heterozygous CFI mutation in patient #1 and a heterozygous MCP mutation in patient #2, and also in her mother who donated the kidney. This finding argues that the two cases originally diagnosed as STEC‐HUS had indeed aHUS triggered by STEC infection on a genetic background of impaired complement regulation. Complement gene sequencing should be performed before kidney transplantation in patients who developed ESRD following STEC‐HUS since they may be undiagnosed cases of aHUS, at risk of posttransplant recurrence. Furthermore, genetic analysis of donors is mandatory before living‐related transplantation to exclude carriers of HUS‐predisposing mutations. Abstract : Two patients with a clinical history of D+ hemolytic uremic syndrome associated with Shiga‐toxin‐producing 0157:H7 E. coli and recurrence in the kidney graft carry heterozygous mutations in the genes encoding complement factor I (patient 1) and membrane cofactor protein (patient 2).